The Effect of Fraud Diamond on Financial Statements of Insurance Companies in Indonesia - Novy Silvia Dewi; Benediktus Tandya Pinasthika (Research Center and Case Clearing House PPM School of Management, 2023)
The Jiwasraya corruption scandal and related cases revealed significant financial distress, opportunities for fraud, rationalization of actions, and the ability to manipulate financial statements, emphasizing the importance of research and awareness in addressing fraudulent financial statements in the insurance industry. This study aims to analyze the impact of the fraud diamond, composed of pressure, opportunity, capability, and rationalization, on corporate financial statement fraud. This study is crucial due to the pressing issue of fraud incidents at several state-owned insurance firms in recent years. An insurance company serves as the sample for this research, using STATA to utilize 55 financial statement observations from 2016-2020, with a research duration of 5 years. The study's findings were not able to establish that the fraud diamond, composed of pressure, opportunity, capability, and rationalization, affects financial statement fraud. This contradicts the results of previous examinations and marks the first instance of rejection of a hypothesis established through regression modeling in this field of study. The occurrence of financial statement fraud may vary among sectors based on the results of this study. This study contributes to understanding fraudulent financial reporting in the insurance industry, emphasizing the importance of pressure and opportunity as key factors.Â